Assessing the impact of forest proximity on household economic well-being in rural Nigeria - Bolaji Kofoworola Adedigba; Oyelowo Oyetayo; Ahmed Olaitan, Ahmed; Adebayo Dorcas Olukemi (Department of Sociology, Faculty of Social Sciences, Gorontalo State University, Indonesia, 2025)
Forests are essential to the welfare of rural households living in areas adjacent to forested regions. This study examines the factors influencing forest resource utilization and their subsequent impact on household welfare. This study examines households in Southwestern Nigeria, offering valuable insights into the relationship between forest resources and rural household well-being. A multistage sampling technique, supported by a structured questionnaire, was employed. Three states with the highest concentration of forests in Southwestern Nigeria were purposively selected. Twenty-five villages—Ogun (15), Ondo (5), and Osun (5)—were randomly chosen in proportion to the size of the forest areas, and 430 households were randomly selected. Descriptive statistics and multiple regression analysis were used to interpret the data. The findings reveal that 92% of the household heads were male, with a mean age of 48 years and a mean household size of 6.92 members. Farming was the primary occupation of 65.30% of the household heads, while 17.90% relied on forest resources as their primary occupation, and 40.70% engaged in forest activities as a secondary source of income. The regression analysis yielded an R² of 0.58, indicating that the explanatory variables accounted for 58% of the variation in per capita expenditure, which serves as a proxy for welfare. Key factors influencing household welfare included education status (0.47), duration of residence (0.12), farm size (0.15), village group membership (0.59), and age (-0.25), with varying levels of statistical significance. This study underscores the critical role of socioeconomic characteristics in shaping household expenditure and, by extension, rural household welfare. Based on the findings, it is recommended that awareness campaigns be launched to promote the sustainable management of forest resources and to encourage their responsible utilization and domestication to prevent resource depletion.